(untitled) (Orchid Academia Siraha, 2024)
This study explores the learning difficulties among students in public secondary schools in Kirtipur municipality. It focuses the availability of instructional materials and the challenges faced by the students while teaching and learning. A quantitative research design was employed, using a structured questionnaire to collect data from 10 secondary-level teachers and 100 students selected through simple random sampling. The findings reveal only 30% of teachers perceive the curriculum is relevant, despite its potential to enhance students’ understanding. While 70% of teachers consider the curriculum comprehensive and capable of preparing students for recent challenges, 30% disagree, citing a lack of real-life applicability. Notably, 20% of them believe the curriculum exceeds the capacity of average students. Additionally, 80% highlight the lack of differentiated exercises in textbooks, making it challenging to cater to diverse student abilities. All participants agree that evaluation procedures need improvement to foster student interest in learning. This study underscores the need for resource investment, and increased teacher training to improve the learning difficulties of students in the public secondary schools in Nepal.